A mobilização política do discurso do herói pioneiro da luta social de 1957 no sudoeste do Paraná - Rippel, Leomar (2012)
This research aims to analyze policies aimed at exalting memory and the institutionalization of regional pioneer as a hero in Paraná. The government instituted struggled the most in the social imaginary constitute a migrant from Santa Catarina and Rio Grande do Sul as a symbol of labor, progress and prosperity. Therefore, the representations of an arduous and heroic past are influencing the naturalization of discourse, in which the notion of society is not always considered as human production, so that there is a process of removal of this perception by subjects who see it as a reality outside the individual, where the individual and society are seen dichotomously. Through this research analyzed the sources such as newspapers, magazines, drama, literary, political speeches and monuments, possible to understand the various forms used to create and galvanize a collective representation of migrant Southerner as the only one capable of leading the southwestern Paraná direction progress. It was felt that way, that to constitute such representations, there was a need to silence the memory of indigenous groups and Caboclos, the first inhabitants of the Southwest Region. So, speeches extolling the achievements of the Southwest Parana, especially after 1970, contributed greatly to the creation of this collective representation, forging identity references in an attempt to produce a set of values and behaviors homogeneous, and control collective time . From the analysis categories as collective memory, social imaginary, social representations, symbolic capital and discourse analysis, this paper seeks to understand this discourse, which served as a way to utilize and represent the past in terms of a present and a future However, it was realized that who better mobilized symbolic resources pioneirista were the ones that designed and perpetuated the political scene regional, state and federal.